HUBUNGAN STATUS GIZI DENGAN HASIL BELAJAR SISWA PUTERA KELAS V SD NEGERI 002 PASAR BENAI KABUPATEN KUANTAN SINGINGI - Bestari Bestari; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, Based on observations by the author and information from teachers at SDN 002 Penjasorkes Pasar Benai Singingi Kuantan District, there are still many students who penjasorkesnya low learning outcomes it is suspected because of the nutritional status of students is different. Therefore, researchers are interested to prove by means of research with nutritional status and the results of relationship the students learn some vital lessons SDN 002 Pasar Benai. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is the nutrition status while the dependent variable (Y) is the result of learning. The data in this study were obtained from the test height and weight to determine the nutritional status while learning the value of MID hail the semester students. Before the data is processed researchers to test data normality test results Liliefors with normal distribution of data. After the data were analyzed using product moment correlation was found the value of r count (-0484,) <rtabel (0.497) can thus be concluded that there is no correlation with the nutritional status of student learning outcomes SDN 002 V class son Pasar Benai Singingi Kuantan District.Keywords: NutritioNl Status, Learning Outcomes